Membangun siswa literat melalui edukasi dan proyek literasi - Sri Hapsari Wijayanti (Riau Journal of Empowerment, 2020)
Reading literacy competence is an educational problem that requires special attention and needs continuously improved. Reading literacy should begin earliest in the family environment. After entering the school, teachers need to work together with parents to raise a reading culture. Public of Elementary School (SDN) Pulau Kelapa 01 Pagi has not involved parents yet before in encouraging students to read. Therefore, the purposes of this activity are to educate parents about the importance of reading literacy and evaluating the Literacy Project assigned to parents. This community service activity uses the method to educate parents with tutorials, discussion, and experience sharing techniques. After opening the mindset and giving the knowledge about literacy reading, participants, namely the parents of 29 fourth grade students, were given a Literacy Project assignment for a week. This activity has increased the attention of parents about the importance of reading and fostering reading through the family environment. However, in fact, in the implementation of the Literacy Project, parents have not yet fully carried out. Parents still need to implement reading habits at home. In this case, the school needs to collaborate with parents in creating a pleasant literacy atmosphere through various literacy activities in a sustainable manner. Universities can help realize these programs.